Laparoscopy and laparotomy combined with bone marrow biopsy in staging Hodgkin's disease. Issue 5996 (6th December 1975) - Spinelli, P; Beretta, G; Bajetta, E; Tancini, G; Castellani, R; Rilke, F; Bonadonna, G
Abstract : The relative merits of laparoscopy with liver and spleen biopsy and staging laparotomy were studied in 91 unselected patients with Hodgkin's disease. Laparoscopy with liver and spleen biopsy were combined with needle biopsy of the bone marrow and laparotomy was combined with open bone marrow biopsy. In 65 untreated patients six out of seven with liver or marrow disease, or both, were shown to have extranodal lymphomas in these sites by laparoscopy plus needle marrow biopsy. Among 26 patients who had been treated this finding occurred in six out of 10 patients. Spleen biopsies during laparoscopy detected infiltration by lymphoma in 14 out of 37 (38%) patients with diseases spleens. Morbidity was higher after laparotomy than after laparoscopy. Laparoscopy produced abdominal bleeding secondary to splenic biopsy in two patients. All patients with Hodgkin's disease should be subjected to laparoscopy plus needle marrow biopsy before undergoing laparotomy.